2022
DOI: 10.7883/yoken.jjid.2022.092
|View full text |Cite
|
Sign up to set email alerts
|

Casirivimab/Imdevimab for Active COVID-19 Pneumonia Which Persisted for Nine Months in a Patient with Follicular Lymphoma during Anti-CD20 Therapy

Abstract: Immunocompromised patients are more likely to develop severe COVID-19, and exhibit high mortality. It is also hypothesized that chronic infection in these patients can be a risk factor for developing new variants. We describe a patient with prolonged active infection of COVID-19 who became infected during treatment with an anti-CD20 antibody (obinutuzumab) for follicular lymphoma. This patient had persistent RT-PCR positivity and live virus isolation for nine months despite treatment with remdesivir and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In a study evaluating the outcomes of various treatments in 31 cases of persistent COVID-19, mostly after BCDT, a combination of remdesivir and either CPT or casirivimab/imdevimab was associated with better chances of symptomatic improvement and viral clearance than remdesivir only [15]. In a few reports, monoclonal antibodies were curative after a very prolonged infection, sometimes unresponsive to recurrent treatments with remdesivir and steroids [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating the outcomes of various treatments in 31 cases of persistent COVID-19, mostly after BCDT, a combination of remdesivir and either CPT or casirivimab/imdevimab was associated with better chances of symptomatic improvement and viral clearance than remdesivir only [15]. In a few reports, monoclonal antibodies were curative after a very prolonged infection, sometimes unresponsive to recurrent treatments with remdesivir and steroids [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Additional methodological details are provided in Figure 1 and in the Supplementary Methods and Supplementary Tables 1, 2 . This review included 19 studies that reported on a total of 24 patients (median age, 54.5 years [interquartile range (IQR) 44–64 years]; 15 male) [ 7 8 9 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ].…”
Section: Systematic Search and Analysis Of Literaturementioning
confidence: 99%
“…In some patients, polymerase chain reaction (PCR) tests for SARS-CoV-2 can yield positive results for approximately 80–300 days from the initial positivity [ 5 6 7 ]. Prolonged SARS-CoV-2 infection poses a public health threat as it may lead to a higher number of viral mutations, potentially resulting in the emergence of drug-resistant variants and variants with increased infectivity [ 8 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, persistent viral shedding in this group of patients raised major therapeutic concerns because antiviral drugs could not eradicate the virus and were responsible for the emergence of mutations, resistance, and new variants [ 13 , 18–20 ]. Several risk factors for persistent viral shedding had been identified, among which are B-cell dysfunction (malignant lymphoma, multiple myeloma, anti-CD20 and anti-CD19 therapies), lymphocytopenia, serum elevation of type 1 interferon, immature neutrophils, delayed antiviral therapy, and D-dimer elevation [ 15 , 16 , 21–23 ]. Persistent viral shedding was associated with a spike protein mutation and an increased risk of bacterial infections and death [ 15 , 16 , 21–23 ].…”
mentioning
confidence: 99%
“…Several risk factors for persistent viral shedding had been identified, among which are B-cell dysfunction (malignant lymphoma, multiple myeloma, anti-CD20 and anti-CD19 therapies), lymphocytopenia, serum elevation of type 1 interferon, immature neutrophils, delayed antiviral therapy, and D-dimer elevation [ 15 , 16 , 21–23 ]. Persistent viral shedding was associated with a spike protein mutation and an increased risk of bacterial infections and death [ 15 , 16 , 21–23 ]. However, the absence of a standardized definition of the duration of “persistence” makes it difficult to interpret and extrapolate previous reports [ 16 ].…”
mentioning
confidence: 99%